Estudo do modelo de percolação de sítios e suas aplicações em eletrodos de baterias - Moraes, Alex Silva de (2018)
The knowledge of how porous electrodes work is of extreme importance for the study of batteries, since they are widely used in industries. The mathematical description currently used for the description of this kind of electrode is Newman’s macro-homogeneous theory, which assumes a homogeneity in the porous structure and works with averages over the electrode. The purpose of the present study was to use the site percolation theory to implement the macro-homogeneous theory by means of statistical results obtained through computer aided simulations and relate the obtained parameters with electrochemical parameters used in the description of porous electrodes. The first part of this study aimed the implementation of a site percolation algorithm based on the model of Chirkov and Rostokin [1] and the results were compared for validation of the algorithm. Then, we interpreted the results for the application on battery electrodes. The study presents an optimal relation between the ionic transport inside the pores and the chemical reactions on its surface as well as an analysis of the conductivity of the positive and negative electrodes taking into account the PbSO4 formation on the pore surface. Finally, a model for the calculation of the parameter a of the macro-homogeneous theory was proposed and compared with other models from the literature. The model presented in this study resembles some of the literature, with the advantage of giving physical meaning to its parameters and not relying on empirical data.